Tumor-associated macrophages of the M2 phenotype contribute to progression in gastric cancer with peritoneal dissemination - Yamaguchi, Takahisa (Gastric Cancer, 2015)
BACKGROUND: Tumor-associated macrophages (TAMs) of the M2 phenotype are known to promote tumor proliferation and to be associated with a poor prognosis in numerous cancers. Here, we investigated whether M2 macrophages participate in the development of peritoneal dissemination in gastric cancer. METHODS: The characteristics of peritoneal macrophages in gastric cancer patients with or without peritoneal dissemination were examined by flow cytometry and the real-time quantitative polymerase chain reaction. The effects of M2 macrophages on phenotypic changes of the gastric cancer cell line MKN45 were assessed with a direct or indirect co-culture system in vitro and an in vivo mouse xenograft model. RESULTS: The number of peritoneal macrophages with the M2 phenotype (CD68(+)CD163(+) or CD68(+)CD204(+)) was significantly higher in gastric cancer patients with peritoneal dissemination than in those without peritoneal dissemination. Higher expression of the M2-related messenger RNAs (IL-10, vascular endothelial growth factor A, vascular endothelial growth factor C, matrix metalloproteinase 1, and amphiregulin) and lower expression of M1-related messenger RNAs (TNF-α, CD80, CD86, and IL-12p40) were also confirmed in the TAMs. Macrophage co-culture with gastric cancer cells converted M1 phenotype into M2 phenotype. Moreover, the coexistence of MKN45 cells with M2 macrophages resulted in cancer cell proliferation and an acceleration of tumor growth in the xenograft model. CONCLUSIONS: Intraperitoneal TAMs in gastric cancer patients with peritoneal dissemination were polarized to the M2 phenotype, and could contribute to tumor proliferation and progression. Therefore, intraperitoneal TAMs are expected to be a promising target in the treatment of peritoneal dissemination in gastric cancer.